Enzyme-Enhanced Symbiotics: A Sustainable Alternative to Antibiotic Growth Promoters in Broiler Chickens - Andrade-Muyulema Erick; Ramírez-Gallardo Bismarck; Cuenca-Condoy Mercy (Revista Electronica de Veterinaria, 2025)
This study evaluated the effect of dietary supplementation with enzyme-enhanced symbiotic on productive, immunological, digestive, and histo-morphological parameters in broiler chickens. The research was conducted under commercial conditions in the Balsas canton, El Oro province (Ecuador), using a longitudinal experimental design. A total of 84,000 birds were randomly allocated to four treatments: T0 (control), T1 (0.01%), T2 (0.03%), and T3 (0.05%) symbiotic, all combined with 0.01% protease enzymes. Productive performance, apparent digestibility, intestinal morphometry, and serum immunoglobulins (IgY, IgM, IgA) were assessed on days 1 and 21 of age. Treatment T2 (0.03%) yielded the best zootechnical performance, with greater weight gain, more efficient feed conversion, and enhanced intestinal mucosal development, as evidenced by increased villus length and density. Additionally, T2 improved crude protein and fat digestibility and significantly stimulated IgM production, suggesting more effective enteric immune activation. In contrast, T3 (0.05%) exhibited negative effects on intestinal morphology and weight gain, indicating that higher concentrations may cause physiological interference. No clear dose-dependent trend was observed for crude fiber and dry matter digestibility. Statistical analysis confirmed significant differences (p < 0.05) among treatments. In conclusion, supplementation with 0.03% symbiotic enhanced with enzymes proved to be the most effective strategy for improving intestinal health, nutrient utilization, and productive performance in broiler chickens, establishing itself as a promising functional alternative for intensive poultry systems.